Crisis and emergency management : theory and practice - Farazmand, Ali (CRC Press, Taylor & Francis Group, 2014)
"More than 12 years have passed since the publication of the first edition of Crisis and Emergency Management. During that time numerous disasters--from 9/11 to massive earthquakes in Iran and China, to the giant Asian Tsunami, Hurricane Katrina, and the Fukushima Tsunami and ensuing nuclear meltdown--have changed the way we manage catastrophic events. With contributions from leading experts, this second edition features 40 new chapters that address recent worldwide crises and what we have learned from emergency responses to them. The book covers a wide range of international issues using critical, empirical, and quantitative analyses. It discusses various approaches to topics such as resolving political tension and terrorism issues, the potential use of biological weapons, and the role of public relations in crisis. The author offers insight into organizational and community resiliency development; a "surprise management" theory in practice for upgrading the knowledge and skills in managing crises and governing emergencies; and better and more effective organizational, political, social, and managerial coordination in the processes. He presents case studies that enhance and advance the future theory and practice of crisis and emergency management, while at the same time providing practical advice that can be put to use immediately"- Resumé vydavatel
Revised edition of Handbook of crisis and emergency management, published in 2001.
Keywords: krizový management -- Spojené státy americké; havarijní plánování -- Spojené státy americké; interkulturní management -- Spojené státy americké; crisis management -- United States; disaster planning -- United States; intercultural management -- United States; elektronické knihy; případové studie; electronic books; case studies